Enhanced removal of indigo carmine dye from aqueous solutions using polyaniline modified partially reduced graphene oxide composite - Saadia M. Waly; Ahmad M. El-Wakil; Mohamed M. Waly; Weam M. Abou El-Maaty; Fathi S. Awad (Scientific Reports)
Abstract In this study, graphene oxide (GO) nanosheets were chemically modified by attaching polyaniline (PAN) nanoparticles to their surfaces, creating a polyaniline partially reduced graphene oxide composite (PAN@PRGO). This synthesized PAN@PRGO nanocomposite serves as an innovative and highly effective adsorbent for removing indigo carmine (IC) dye from water. The morphology and chemical composition of PAN@PRGO were analyzed using various techniques, including scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS), confirming the successful grafting of PAN onto the GO surface. Batch adsorption tests showed that PAN@PRGO has an outstanding adsorption capacity for indigo carmine (IC) dye, achieving 490.0 mg g−1 at pH 5.0 and 298 K. This is notably higher than the adsorption capacity of GO nanosheets alone (317.25 mg g−1) and exceeds that of other materials reported in the literature. Additionally, PAN@PRGO demonstrated 100% removal efficiency for IC dye at concentrations up to 300 mg L−1. The experimental data closely matched the Langmuir isotherm model and the pseudo-second-order kinetic model, suggesting that electron-sharing interactions between IC dye and PAN@PRGO contribute to the adsorption mechanism. The adsorbed IC dye was recoverable using a 0.1 M NaOH solution, with the composite retaining near-100% efficiency even after five adsorption–desorption cycles. These results indicate that the PAN@PRGO composite is a promising, reusable adsorbent for effective IC dye removal from industrial wastewater.